2016
DOI: 10.1039/c5cy01259g
|View full text |Cite
|
Sign up to set email alerts
|

Polynuclear gold(i) complexes in photoredox catalysis: understanding their reactivity through characterization and kinetic analysis

Abstract: The light mediated reduction of unactivated carbon–halogen bonds using polynuclear gold(i) complexes provides a mild and temporally controlled route to the generation of C–H, and C–C bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 65 publications
0
61
0
2
Order By: Relevance
“…Comprehensive optimization revealed that quantitative conversion of 1 to 2a can be achieved with only 2equivalents of the alkyl iodide,1 5mol %M n 2 (CO) 10 ,a nd 0.1 equivalents of TFA (Table 1, entry 6, see the Supporting Information for the full optimization table). [1][2][3][4][5][6][7][8] Also noteworthy is the fact that the use of an unactivated alkyl bromide did not result in CÀHa lkylation of lepidine 1 (See Figure 2c). [1][2][3][4][5][6][7][8] Also noteworthy is the fact that the use of an unactivated alkyl bromide did not result in CÀHa lkylation of lepidine 1 (See Figure 2c).…”
Section: Entry 2)mentioning
confidence: 98%
See 3 more Smart Citations
“…Comprehensive optimization revealed that quantitative conversion of 1 to 2a can be achieved with only 2equivalents of the alkyl iodide,1 5mol %M n 2 (CO) 10 ,a nd 0.1 equivalents of TFA (Table 1, entry 6, see the Supporting Information for the full optimization table). [1][2][3][4][5][6][7][8] Also noteworthy is the fact that the use of an unactivated alkyl bromide did not result in CÀHa lkylation of lepidine 1 (See Figure 2c). [1][2][3][4][5][6][7][8] Also noteworthy is the fact that the use of an unactivated alkyl bromide did not result in CÀHa lkylation of lepidine 1 (See Figure 2c).…”
Section: Entry 2)mentioning
confidence: 98%
“…Gratifyingly,i tw as found that this mild protocol tolerates simple to relatively complex functionalized primary (2b-2g), secondary (2h-2q), and tertiary (2r-2s)u nactivated iodoalkanes in moderate to excellent yields (19-98 %). [2,[4][5][6][7] Furthermore,t his technology was fully applied to other heterocyclic cores (pyridine,phthalazine,and benzimidazole) (Table 2b, 3-6,4 3-60 %y ield). [3] Them ildly acidic conditions allowed the introduction of acid-sensitive groups,s uch as oxetane,asugar moiety,a zetidine,a nd tert-butyl carbamate (Boc group), which provide synthetic handles for further derivatization and structure-activity relationship (SAR) studies ( Table 2, 2g, 2j, 2k, 2l, 2o, 2q, 3, 4,and 5).…”
Section: Entry 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…[132] Da auch photoangeregtes [Au 2 (dppm) 2 ]Cl 2 Alkylbromide durch einen photoinduzierten Innensphären-SET reduzieren kann (Schema 55, mechanistische Überlegungen), [133] nahmen die Autoren an, dass sich dieser Ansatz auch in einen insgesamt redoxneutralen Minisci-Mechanismus integrieren lässt. [132] Da auch photoangeregtes [Au 2 (dppm) 2 ]Cl 2 Alkylbromide durch einen photoinduzierten Innensphären-SET reduzieren kann (Schema 55, mechanistische Überlegungen), [133] nahmen die Autoren an, dass sich dieser Ansatz auch in einen insgesamt redoxneutralen Minisci-Mechanismus integrieren lässt.…”
Section: Angewandte Chemieunclassified